ASK-LOM-AT 2.0: A web-based tool for educational metadata authoring of open educational resources - Sampson, Demetrios; Zervas, P.; Chloros, G. (2011)
A number of international initiatives, such as the leading initiative of Open Educational Resources (OER) movement, have recognized the potential value of sharing and reusing digital resources among educational communities. As a result, organizing, managing, offering and accessing these resources over the web have been key issues for both the research and the educational community. Within this context, over the past years a number of international efforts have led to the development of the IEEE LOM standard as a commonly accepted way for describing educational resources with metadata, facilitating storage, search and retrieval of these resources through web-based repositories. In response to this increased interest, a number of software tools have been developed, so as to facilitate educational metadata authoring of educational resources. However, these tools have a number of limitations, adding extra barriers to the widespread deployment of this process. In this paper, we aim to address this problem by introducing a new web-based tool (ASK-LOM-AT 2.0) that aims to overcome the identified limitations of existing tools and simplify the process of educational metadata authoring for educational resources following the IEEE LOM standard. © 2011 IEEE.